Unlawful Dividends, Unjust Enrichment, and the Defence of Change of Position - MACRAE, Cecil Duncan (Institutional Knowledge at Singapore Management University, 2005)
Economic analysis is applied to determining the effect of the change of position defense on the question of whether an innocent shareholder receiving an unlawful, mistaken dividend should be liable under English restitution law as the result of unjust enrichment. The analysis builds on and extends previous economics analysis of mistaken money transfers under restitution law. The conclusion of the analysis of the change of position defense is that unjust enrichment liability with the defense should not be extended to unlawful, mistaken dividends, even if the factors for unjust enrichment are present.